Learning Trends in the Knowledge Age: Changes in Patterns and Learning Technologies - Hasmidyani, Dwi (Technium Social Sciences Journal, 2021)
The rapid development of technology and information in this knowledge age has an unavoidable influence on the field of education. The development of science and technology has consequences for the demands of human resources (HR) with good quality. Changing the learning paradigm pattern is needed in order to create human resources that are able to compete globally. The learning pattern in the knowledge age focuses more on independence in learning (student center), proficiency in using technology, an open, flexible and limitless learning process, collaboration, and the ability to carry out investigation and design.